Analisis Perhitungan Pajak Penghasilan Pasal 21 Tahun 2022 pada Perusahaan X di Bekasi - Saputra, Aji; Huda, Miftakul; Karmilah, Karmilah; Putri, Risa Mutiara Purnama (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
Taxes are one of the main sources of state income, and tax on individual income is one type of tax applied in Indonesia. The government imposes Income Tax (PPh) Article 21 on every individual who receives income from their work. The company where the individual works is responsible for calculating, withholding and recording the PPh, then depositing it to the government and reporting it to the Tax Service Office (KPP). The aim of this research is to analyze the tax calculations carried out by the company. The method used in this research is a descriptive method, namely by collecting, processing and presenting observation data that describes the characteristics of objects. The data used in this research consists of two categories, namely qualitative and quantitative data. The research results show that the calculation of PPh Article 21 for company X in Bekasi for 2022 is in accordance with Law no. 36 of 2008 concerning Income Tax and have carried out the calculation of Article 21 correctly.